Determination of Half-life of Dissolution Process of Oxaliplatin in DMSO - Suo, J.L.; Pu, X.H.; Zhao, W.W. (Asian Journal of Chemistry, 2014)
The enthalpies of dissolution for oxaliplatin in dimethyl sulfoxide were measured using a RD496-CK2000 calve microcalorimeter at 309.65 K under atmospheric pressure. Differential enthalpies and molar enthalpies were determined for oxaliplatin in dimethyl sulfoxide, then the relationship of the heat effect of each process with the amount of the substance was setted up. On the basis of the dynamics equation, the process of dissolution is a pseudo first order reaction was indicated. Meanwhile, the half-life period t1/2 = 59.32 min, the molar enthalpy DsolHm = 14.996 kJ mol-1, the molar gigs free energy DsolGm = 97.93 kJ mol-1, the molar entropy is DsolSm = -267.81 J mol-1 K-1 were calculated. The result not only provides a simple method for the detemination of the half-life for drugs, but also offer a theoretical reference for the clinical application of oxaliplatin